Investigating correlates of aggressive behaviour in South African children and young adolescents living in the Western Cape: the role of empathy - Pileggi, Lea-Ann (Department of Psychology, 2018)
Escalating rates of aggression in South African schools, particularly in the Western Cape, are disconcerting. The early childhood through adolescent years is therefore an important platform for investigations to inform strategies to reduce and prevent aggressive behaviour. Studies conducted outside of South Africa have identified numerous correlates of aggressive behaviour; investigation in South Africa has, however, been sparse. The role of empathy, in specific, has been limited to one prior investigation. Furthermore, while empathy is considered an important construct in explanations of aggressive behaviour internationally, theoretical and methodological issues have undermined findings to date. Our understanding of the relationship between empathy and aggressive behaviour needs refining. I investigated the role of empathy, while simultaneously investigating the role of several known correlates of empathy and aggressive behaviour in typically developing young adolescents (N = 160, ages 11-13; Study 1) and children (N = 76, ages 6-8; Study 2) living in the Western Cape of South Africa. To improve on previous investigations, I employed a framework informed by both neurobiological and behavioural approaches. I conceptualised empathy as comprising affective and cognitive components, as well as a self-regulation component concerned with regulation of affective states. Employing a contextual approach, I argued that the interaction between these empathy components along with multiple contextual factors would provide a more nuanced understanding of the relationship between empathy and aggressive behaviour. I used hierarchical regression and structural equation models to investigate the correlates of aggressive behaviour. Empathy was significantly correlated with Aggressive Behaviour in young adolescents, but not in children. Furthermore, as expected, contextual factors were also significantly correlated with Aggressive Behaviour: Household Income, Parenting Style, and Parent Empathy were correlated with Aggressive Behaviour in young adolescents, while among the measures taken only Parenting Style was correlated with Aggressive Behaviour in children. Future investigations should, as in the current dissertation, work towards articulating the complex web of relationships between correlates of aggressive behaviour and their changes across development.